Intellectual Security and Its Relationship to Both Suggestability and the Tendency to Deal with Rumors among University Students - Ahmed, S, Al-Mutawa,; Yahya, M, Khatatbeh, (Journal of Ecohumanism, 2024)
Objectives::The study aimed to identify the level of susceptibility to suggestion, the most common among students of Imam Muhammad bin Saud Islamic University, and to determine the prevailing trend they have in dealing with rumors, in addition to revealing the relationship between intellectual security and suggestibility, the study relied on the descriptive and comparative approach to reveal the relationship between intellectual security and both suggestability and the trend towards dealing with rumors Methodology: Participants the study sample consisted of (300) university students. To achieve the objectives of the study, motheds: the intellectual security scale prepared by Al-Qarni (2019) and the suggestability scale prepared by (Watson & Watson, Bellman, 2004, Kotov, translated by Al-Shorbagy and Al-Harbi (2016) were used. The Measure of Trend in Dealing with Rumors by Al-Harbi (1991) results of the study indicated that the level of intellectual security among students of Al-Imam Muhammad bin Saud Islamic University came with a high degree with an arithmetic average (4.15), and that the level of suggestability among students of Al-Imam Muhammad bin Saud Islamic University was average, as it came with an arithmetic average (1.98), and that the level of tendency towards rumors among students of Al-Imam Muhammad bin Saud Islamic University was average, where it came with an arithmetic average of (1.71). The results also showed that there is no predictability of suggestability through intellectual security among university students, and it was clear that there is a predictability of the trend towards dealing with rumors through intellectual security among university students, and the results of the study also showed a relationship between the variables of the study (intellectual security and its dimensions, suggestibility and sub-dimensions, and the trend towards dealing with rituals) where it was found that there was a statistically significant positive relationship between them. Finally, the most prominent recommendations of the study were to draw the attention of researchers to conduct analytical and qualitative studies to deal with rumors among students, specifically rumors spread through social media.